HUBUNGAN PIJAT BAYI MANDIRI DENGAN POLA MENYUSUI PADA BAYI ASI EKSKLUSIF - Ranti Yuliana; Debora Paninsari; Wulan Sekar Sari; Nisaul Mudrikah; Elli Airi; Reska Elisa (Jurnal Ilmiah Kebidanan Imelda, 2026)
Regularly massaging babies can optimize breast milk intake, appetite, and weight gain. This consistent touch therapy is key to obtaining comprehensive health benefits for babies. This study was designed to analyze the relationship between baby massage practices performed independently by mothers and the consistency of breastfeeding patterns in babies who are exclusively breastfed. This study applied a quantitative approach with an analytical observational design through a cross-sectional design. A total of 110 mothers with infants aged 0-12 months at Teungku Peukan General Hospital were included in this study. Using purposive sampling, a sample of 86 respondents was obtained. Data were collected through a structured questionnaire to assess the variables of independent infant massage and exclusive breastfeeding patterns, which were then analyzed using the Chi-Square statistical test. The results of the study revealed that 65.1% of respondents performed independent infant massage and 61.2% of mothers had good breastfeeding patterns. Statistically, a significant relationship was found between the practice of independent infant massage and breastfeeding patterns in exclusively breastfed infants, as indicated by a p-value of 0.000 (p<0.05). Thus, it can be concluded that massage stimulation by mothers contributes to the success of breastfeeding patterns.